A comparison of upland stream invertebrates in moorland and coniferous woodland in North York Moors National Park, UK. Issue 2 (3rd April 2017) - Jones, Sam; Mayhew, Peter J.
Abstract: Conversion of moorland to coniferous woodland is a common land use change in the high latitude uplands. Conifer woodlands are known to increase detrimental acidification in upland streams but can benefit some invertebrates by increasing allochthonous inputs. We aimed to identify the effects of conifer woodlands on benthic stream macroinvertebrate communities in North York Moors National Park, which has some of the most acidified streams in the United Kingdom. Benthic invertebrates from 8 moorland and 8 conifer woodland catchments were gathered using kick sampling in 2014. Taxonomic composition and diversity differed significantly in woodlands and moorlands, with woodland communities showing higher diversity and species characteristic of lower levels of stressors. Moorland and woodland communities did not differ in average acid sensitivity, and taxa were typical of close-to-neutral pH, matching spot pH measurements taken during sampling that were 2–3 pH units higher than in 2005. We conclude that conversion of moorland to coniferous woodland does not necessarily detrimentally affect upland stream invertebrate communities, and that those on the North York Moors are not always highly acid-tolerant, perhaps indicating biotic recovery from previous acidification.